Cation exchange membrane by radiation-induced grafting of styrene onto polpypropylene : Effect of grafting conditions - Ngah, Tengku Ida Sofina; Nasef, Mohamed Mahmoud; Saidi, Hamdani; Dahlan, Khairul Zaman M. (2004)
In a first step towards preparation of cation exchange membrane, styrene monomer was grafted onto polypropylene (PP) film using simultaneous radiation-induced grafting technique. The effect of monomer concentration and irradiation dose on the degree of grafting was investigated. The grafting yield was found to increase until 40 % monomer concentration and beyond which tends to level off. The degree of grafting was found to increase gradually to the irradiation dose. The obtained grafted PP films (PP-g-PS) were characterized by FTIR-ATR to confirm the presence of polystyrene grafts in the PP films.